The musical art of synthesis - McGuire, Sam; Rest, Nathan van der (Focal Press, 2016)
New synths with unique features and layers of complexity are released frequently, with hundreds of different synths currently available in the marketplace. How do you know which ones to use and how do you get the most out of the ones you already own? The Musical Art of Synthesis　presents synthesizer programming　with a　specific focus on synthesis as a musical tool.　Through its innovative design, this title offers an applied approach by providing a breakdown of synthesis methods by type, the inclusion of step-by-step patch recipes, and extensive web-based media content including tutorials, demon
Keywords: Synthesizer (Musical instrument) : Instruction and study; Electronic music : Instruction and study